The ASEAN-China free trade zone challenges and opportunities for ASEAN - Tambunan, Tulus (The Philippine Review of Economics, 2006)
This paper assesses the implication of 'ASEAN plus China' on ASEAN inter- and intra-trade. Based on secondary data analysis and survey of key literature, it shows a number of interesting findings. First, despite the establishment of the ASEAN Free Trade Area, regions outside ASEAN are still the most important markets for individual member countries, for both export and import. Second, recent data show that after the United States, the European Union, and Japan, China tends to become ASEAN?s largest trading partner; trade between China and ASEAN continues to increase, and its rate tends to accelerate. Third, based on various analytical approaches, the implementation of ASEAN plus China will most likely lead to trade diversion (TD), at least to some member countries. The paper concludes, therefore, that the ASEAN-China free trade zone will most likely generate higher trade volume between China and ASEAN at the cost of ASEAN intra-trade.